Team selection strategies for major international target archery competitions - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2026)
Results from major international target archery competitions from 1995 to 2023 have been used to show the score trends and the probability of winning either a podium position or the event versus the archer`s position in a ranking round. The probabilities versus ranking position fall approximately exponentially. Subjectively, archers need to rank at least in the top 16 to have a reasonable probability of winning a medal. Ideally, a team selection process should select those archers with the highest probabilities of winning at least a podium position at the international competition. That can be achieved by using the arrow value scores over the entire selection process, providing bonuses for exceeding given scores in ranking rounds or matches and by not including elimination matches in the selection process.